THE IMPORTANCE OF IMPLEMENTATION OF ENVIRONMENTAL LAW IN EFFORTS TO PRESERVE NATURAL RESOURCES IN INDONESIA - Rika Riyanti (ADISAM Publisher, 2023)
Indonesia has many natural resources, including forests, marine biodiversity, and minerals. However, these resources face increasing pressures from economic development, population growth, and climate change. Effective implementation of environmental law is crucial to promote sustainable development, protecting the environment, and preserving natural resources in Indonesia. This study explored the Awareness, enforcement, and community participation related to environmental law, the role of Government, NGOs, and the importance of sustainable development. Data was collected through a review of existing literature and interviews with 45 participants from various sectors. The study's findings suggested that while most participants were aware of environmental laws and regulations, enforcement needed to be stronger and faced obstacles such as corruption and lack of political will. Community participation was seen as essential for effective environmental management, and there was a need for stronger partnerships between the Government and NGOs. The study highlights the need for a robust legal framework to support environmental protection and sustainable development in Indonesia.